Métaphores et représentations du cerveau plurilingue: conceptions naïves ou construction du savoir?: Exemples dans le contexte d’enseignement andorran - Marquillo Larruy, Martine (My University, 2000)
This article concentrates on the use of metaphors characterizing a multilingal brain in a corpus of oral interactions drawn from the Andorran part of the international research to which this issue of the review Tranel is devoted.We first question the situation and the status of metaphors in fields connected to the elaboration of knowledge. We then recall what the most important metaphors associated to the representations of the brain (bilingual or not) can be. Finally, the analysis deals with the metaphors of the Andorran corpus. Their nature and function are observed, both from the point of view of the representations thus created and from that of the elaboration of a common knowledge, necessary to the discourse economy of the group.